(1)依题意:f(x)=lnx+x 2-bx
∵f(x)在(0,+∞)递增
∴ f′(x)=
1
x +2x-b≥0 对x∈(0,+∞)恒成立
∴ b≤
1
x +2x
∵x>0
∴
1
x +2x≥2
2 当且仅当 x=
2
2 时取“=”,
∴ b≤2
2 ,
且当 b=2
2 时, x∈(0,
2
2 ),f′(x)>0 , f′(
2
2 )=0 , x∈(
2
2 ,+∞),f′(x)>0
∴符合f(x)在(0,+∞)是增函数∴ b∈(-∞,2
2 ]
(2)设t=e x,
∵x∈[0,ln2]
∴1≤t≤2,
则函数g(x)化为: y= t 2 +bt=(t+
b
2 ) 2 -
b 2
2 ,t∈[1,2]
①当 -
b
2 ≤1 时,即 -2≤b≤2
2 时.y在[1,2]递增∴当t=1时,y min=b+1
②当 1<-
b
2 <2 时,即-4<b<-2,当 t=-
b
2 , y min =-
b 2
4
③当 -
b
2 ≥2 ,即b≤-4时,y在[1,2]递减,当t=2时,y min=4+2b
综上: g(x ) min =
4+2b
b≤-4
-
b 2
4
-4<b<-2
1+b
-2≤b≤2
2
(3)∵a 1=1,a 2=ln1+1+2=3>1,a 3=ln3+3+2>1
假设a k≥1(n≥1),则a k+1=lna k+a k+2>1,∴a n≥1成立
设F(x)=lnx-x+1,(x≥1),则 F′(x)=
1
x -1<0
∴F(x)在[1,+∞]单调递减,∴F(x)≤F(1)=0,∴lnx≤x-1
∴lna n≤a n-1,故a n+1≤2a n+1,∴a n+1+1≤2(a n+1)a n+1+1≤2(a n+1)≤2 2(a n-1+1)≤≤2 n(a 1+1)=2 n+1,
∴a n+1≤2 n⇒a n≤2 n-1